TRIANGULAR FRAMEWORK FOR TUBERCULOSIS REDUCTION POLICY IN SERANG REGENCY IN 2021-2023 - Seme, Bulan Indah Putri; Deliarnoor, Nandang Alamsah; Kartini, Dede Sri (Universitas Negeri Semarang, 2025)
The main objective of this research is to analyze health policy collaboration, program innovation, and challenges faced in preventing tuberculosis in Serang Regency using a triangle framework. Unlike previous studies that often focus on single-actor initiatives, this research emphasizes the multi-stakeholder collaboration involving regional government and private-sector volunteers. The urgency of this study lies in the persistent burden of TB in Indonesia, particularly in Serang Regency, which requires integrated and adaptive policy innovation. A qualitative method was employed through desk reviews and semi-structured interviews with key stakeholders, with data triangulated for validation. Findings indicate that the innovation programs introduced by the Serang Regency Government—such as active case finding and community-based treatment—have contributed to a decrease in TB incidence, with case discovery rates declining from 230 per 100,000 population in 2021 to 198 in 2023. However, challenges remain, particularly in implementing Tuberculosis Preventive Therapy (TPT) for household contacts. Strengthening inter-sector coordination, expanding service access, and optimizing policy innovation are critical for sustaining progress.